Distributive Justice for Others, Collective Angst, and Support for Exclusion of Immigrants. Issue 6 (15th May 2014) - Lucas, Todd; Rudolph, Cort; Zhdanova, Ludmila; Barkho, Evone; Weidner, Nathan
<x xml:space="preserve">Abstract</x> Harsh treatment of others can reflect an underlying motivation to view the world as fair and just and also a dispositional tendency to believe in justice. However, there is a critical need to refine and expand existing knowledge, not only to identify underlying psychological processes but also to better understand how justice may be implicated in support for exclusionary policies. Across two studies, we show that support for policies that restrict immigrants is exclusively associated with thoughts about fair outcomes for other people (distributive justice for others). In Study 1, Americans' dispositional tendency to believe in distributive justice for others was associated with greater support for a policy proposing to further restrict immigrant job seekers' capacity to gain employment in the United States. In Study 2, we experimentally primed thoughts about justice in a sample of U.S. police officers. Support for a policy that mandated stricter policing of illegal immigration was strongest among officers who first thought about fair outcomes for other people, relative to other unique justice primes. Across both studies, distributive justice for others was associated with greater collective angst—perceived threat towards the future existence of Americans. Moreover, collective angst mediated the link between distributive justice for others and support for restrictive policies. Overall, this research suggests that thoughts about distributive justice for others can especially diminish compassion towards immigrants and other underprivileged groups via support for exclusionary policies. In addition, merely thinking about distributive justice for others may be sufficient to amplify social callousness.